Rancangan Optimasi Proses Manufaktur Heatsink Pendingin Elektrik TEC1-12706 untuk Pendingin Mesin CNC-MILLING Berdasarkan Material yang Digunakan - Rahmat Alfian Fadhillah, (2020)
Increasing human needs in the automotive industry sector in the manufacturing sector continues to increase, manufacturing companies that have the activity of buying a raw material and processing it into a product by using a CNC machine continuously, causing over heating in the engine causing a decrease in engine performance. The design of the TEC1-12706 electric cooling device by comparing the use of copper (Cu) external heatsinks with copper (Cu) based heatsinks and aluminum fins (Al), aims to reduce heat in CNC machines especially in electrical panel components, by optimizing in terms of heatsink material to be used, the manufacturing process of making an electric cooling design by using a solidwork application design as well as in terms of manufacturing economics. The test results show that the temperature difference ratio of an electric cooling system that uses copper heatsink with copper and aluminum heatsink is 1 ̊C, where copper heatsinks are superior in absorbing heat, but are expensive in terms of the economics of the manufacturing process compared to aluminum heatsinks.